2005
DOI: 10.1038/sj.npp.1300810
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Exposure of Rats to Cognition Enhancing Drugs Produces a Neuroplastic Response Identical to that Obtained by Complex Environment Rearing

Abstract: Recent data suggest that Alzheimer's patients who discontinue treatment with cholinesterase inhibitors have a significantly delayed cognitive decline as compared to patients receiving placebo. Such observations suggest cholinesterase inhibitors to provide a diseasemodifying effect as well as symptomatic relief and, moreover, that this benefit remains after drug withdrawal. Consistent with this suggestion, we now demonstrate that chronic administration of tacrine, nefiracetam, and deprenyl, drugs that augment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…FGF2 binding of impaired polySia biosynthesized in such brains might be expected in schizophrenic brains. The expression of polySia is reported to change depending on drug usage (47) and alcohol exposure (48). The quality and quantity of polySia might be well regulated on cell surfaces, and the concentration of polySia-binding molecules may be finely tuned to activate or inactivate cells through receptors spatiotemporally, likely in conjunction with other regulatory molecules, such as HS.…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 binding of impaired polySia biosynthesized in such brains might be expected in schizophrenic brains. The expression of polySia is reported to change depending on drug usage (47) and alcohol exposure (48). The quality and quantity of polySia might be well regulated on cell surfaces, and the concentration of polySia-binding molecules may be finely tuned to activate or inactivate cells through receptors spatiotemporally, likely in conjunction with other regulatory molecules, such as HS.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and quantity of polySia-NCAM might be strictly regulated. In this regard, imbalances of the polySia expression on NCAM due to low activity or altered expression levels of STX bring about serious consequences for neuronal function and brain diseases other than schizophrenia, such as Alzheimer disease (58,59), Parkinson disease (60,61), and drug abuse (62).…”
Section: Discussionmentioning
confidence: 99%
“…It is not always clear whether they do so by curing the damage or by amplifying (enhancing) capacities that compensate for the loss, or whether the distinction is even always meaningful. Comparing chronic exposure to cognition-enhancing drugs with an enriched rearing environment, one study in rats found that both conditions improved memory performance and produced similar changes in the neural matter (Murphy et al 2006). The improvements in the drug-treated group persisted even after cessation of treatment.…”
Section: Education Enriched Environments and General Healthmentioning
confidence: 99%